الصّورة الشّعرية في المجموعة القصصية (جنية البحر) لجميلة زنير - بالعيد، سهام, معتوق، مبروكة; ولابي، مروة (University of El-oued, 2022)
تهدف هذه الدّراسة إلى البحث عن الصّورة الشّعرية في المجموعة القصصية (جنية البحر) لجميلة زنير، وإذ وقع الاختيار على هذا الموضوع لقلة الدّراسات حوله والانتشار الواسع لفن القصّة القصيرة في الجزائر، يقوم هذا البحث عن المنهج البنيوي، الّذي يساعد في تقنيات بنية القصّة القصيرة، والبحث في بنى النّص، والمنهج الأسلوبي للبحث في الجانب البلاغي (استعارة، كناية، تشبيه)، والمنهج السيميائي للوصول للدّلالات الكامنة في النّص خاصة على مستوى العنوان، والمنهج السوسيولوجي الّذي يربط علاقة المجتمع بالعمل الأدبي مستعينين في ذلك بآليات الوصف التحليلي. ولبلوغ ذلك استند البحث على خطة تضمنت مدخلا وفصلين، مدخل يبحث في مفاهيم حول الصّورة الشّعرية، تناولنا فيه مفهوم الصّورة الشّعرية عند الغرب والعرب بأنواعها وأهميتها وتناولنا في الفصل الأول تجلّيات الصّورة الشّعرية في البناء السّردي للمجموعة القصصية "جنية البحر" لجميلة زنير، بين عتبة العنوان وجمالياته، تطرقنا فيه لدراسة العنوان والبنى السّردية من: زمان، مكان، شخصيات وخصائص الصّورة الشّعرية استهلال وتكثيف واللغة الرمزية، أما بالنسبة للفصل الثاني، فكان عبارة عن دراسة للمكونات الأسلوبية والبلاغية للصّورة الشّعرية في المجموعة القصصية (جنية البحر) لجميلة زنير من ثنائيات ضّدية والصّورة التّكرارية، الاستعارة، الكناية، التّشبيه، وصورة الواقع والخيال وكذلك توظيف الصّورة التّناصية توصّل هذا البحث إلى مجموعة من النّتائج المهمة: هو أنّ الكاتبة جميلة زنير أبدعت في توظيف الصّورة الشّعرية في مجموعتها القصصية بامتياز، والتوظيف الجمالي للتقنيات السّردية بفنية عالية، اهتمامها البالغ بموضوع المرأة الجزائرية وما تعانيه في الواقع ومحاولة إيجاد الحلول حتّى وإن كان بتوظيف الخيال وفي الأخير نرجو أن نكون قد وفقنا في هذه الدراسة وتسليط الضوء على كتاب القصّة القصيرة في الجزائر خاصة المرأة. This study aims to research the poet in the collection of stories (Fairy Sea) by Djamela Zennir, and while this subject was chosen for the lack of studies on this subject and the wide diffusion of the art of the short story in Algeria, this research is based on the structural approach, which helps in the techniques of the structure of the short story, research into the structures of the text, the stylistic approach to research in the rhetorical aspect (metaphor, analogy), the semiotic approach to reach the connotations inherent in the text, in particular at the level of the text. title, and the sociological approach that links the relationship of society to the literary work, using analytical description machines. To achieve this, the research was based on a plan that included an introduction and two chapters, an introduction which examines the concepts on the poet, in which we have dealt with the concept poet when the West and Arabs of all kinds and their importance, and in the first chapter we dealt with the manifestations of the narrative structure, between the threshold of the title and the structure narrative, in which we approached the study of the title and the structures narratives of: time, place, characters and characteristics of the initiation and of the intensification of the poet and symbolic language. As for the second chapter, it was a study of the components stylistics and rhetoric of the poet of the collection of stories (Fairy Sea) by Djamela Zennir, based on the duality of antithesis and the image of repetition, metaphor, metonymy, analogy and the image of reality and fiction, as well as the use of the image of repetition. This research get the important results: It is that the writer Djamela Zennir excelled in the use of the poet in its quintessential collection of stories, the aesthetic use narrative techniques with great art, his great interest in the subject Algerian women and what they actually suffer and trying to find solutions even using fiction and in the end we hope have succeeded in this study and highlight the book of the new in Algeria, especially women.
Keywords: جميلة زنير، الصّورة الشّعرية، جنية البحر، سرد; Djamela Zennir, poetic style, Fairy Sea, narrate